Bioacoustics characterization and habitat use of glass frogs in El Salvador (UNED Research Journal, 2022)
Introduction: Glass frogs occur from Mexico to South America, and, their taxonomy and distribution are currently debated. In El Salvador, the only species is thought to be Hyalinobatrachium fleischmanni, but it may instead be Hyalinobatrachium viridissimum. In any case, the species is scarcely recorded and understudied. Objective: To estimate the species distribution in the Río Lempa basin, and to compare its call with available records. Methods: We used local volunteers to sample 53 sites in Cabañas and Morazán, El Salvador, during the rainy season (September to November); these were visited once in 2019 and once in 2020. Volunteers counted individuals along transects from 6 to 8 pm and recorded some calls with cell phones. Results: We counted 361 individuals, added 53 new localities (mainly deciduous broad-leaved forest and agricultural systems). Abundance was more related with elevation and forest cover, than with river characteristics. Our evaluation of 32 calls found differences in the peak frequency between these glass frog populations and those of H. fleischmanni and H. viridissimum comb. nov. Conclusion: Salvadorian glass frogs are more widespread than previously recorded, their distribution is more related with elevation and forest than with rivers types, and their taxonomic status remains unsolved.
Keywords: Amphibians; Central America; Centrolenidae; conservation; citizen science; distribution